Quantitative efficacy and fate of mesenchymal stromal cells targeted to cardiac sites by radiofrequency catheter ablation - Malik, Rizwan; Darche, Fabrice Fernand; Rivinius, Rasmus; Seckinger, Anja; Krause, Ulf; Koenen, Michael; Thomas, Dierk; Katus, Hugo; Schweizer, Patrick Alexander (Cell transplantation, 2020)
Engraftment and functional integration of stem cells or stem cell-derived cells within cardiac tissue is an important prerequisite for cell replacement therapy aiming at the treatment of heart disease. Recently, a novel intravenous approach for application of mesenchymal stromal cells (MSCs) to cardiac sites has been established using radiofrequency catheter ablation (RFCA)-guided targeting, bypassing the need for open chest surgery or direct myocardial cell injection. However, little is known about the quantitative efficacy and longevity of this strategy. We performed selective power-controlled RFCA with eight ablation pulses (30 W, 60 s each) to induce heat-mediated lesions at the right atrial appendices (RAAs) of pigs. Different concentrations of human bone marrow-derived MSCs (10(5) to 1.6 x 10(6) cells/kg bodyweight) labeled with superparamagnetic iron oxide (SPIO) particles were infused intravenously in nine pigs one d after RFCA treatment and hearts were explanted 8 d later to quantify the number of engrafted cells. Prussian blue staining revealed high numbers of SPIO-labeled cells in areas surrounding the RFCA-induced lesions. Cell numbers were evaluated by quantitative real-time polymerase chain reaction using specific primers for human MSCs (hMSCs), which indicated that up to 10(6) hMSCs, corresponding to similar to 3.9% of the systemically applied human cells, engrafted within the RAAs of RFCA-treated pigs. Of note, infused hMSCs were observed in nontargeted organs, as well, but appeared at very low concentrations. To assess long-term deposition of MSCs, RAAs of three pigs were analyzed after 6 months, which revealed few persisting hMSCs at targeted sites. RFCA-mediated targeting of MSCs provides a novel minimal invasive strategy for cardiac stem cell engraftment. Qualitative and quantitative results of our large animal experiments indicate an efficient guidance of MSCs to selected cardiac regions, although only few cells remained at targeted sites 6 mo after cell transplantation.
Gesehen am 27.11.2020